Sound and Light - Sepehri, Sandy; Nang Chan Yeema (Los Angeles, California, United States Fitzgerald Books, 2007)
Easy text and photographs introduce the physical science of sound and light, including what they are and how hey play i n everyday life
Keywords: Juvenile Nonfiction